Environmental Health Literacy and Clean and Healthy Living Behavior Teaching Practices among Early Childhood Teachers: Mediating Role of Teaching Self-Efficacy - Edi Hasan; Muhammad Nasir; Muhammad Wajdi; Usman Usman (PG PAUD Universitas Islam Makassar | LP2M-UIM | PPJ PAUD (Perhimpunan Pengelola Jurnal PAUD) Indonesia, 2026)
Implementing Clean and Healthy Living Behavior (CHLB) in early childhood education requires teachers with adequate Environmental Health Literacy (EHL) and strong Teaching Self-Efficacy (TSE). However, empirical evidence explaining how EHL translates into CHLB instructional practices remains limited. This study examined the effect of EHL on CHLB instructional practices, with TSE as a mediating variable. A quantitative explanatory research design was employed involving 150 kindergarten teachers from 53 kindergartens in Rappocini District, Makassar, Indonesia, selected through cluster sampling. Data were collected using a structured questionnaire measuring three latent constructs: Environmental Health Literacy, Teaching Self-Efficacy, and CHLB instructional practices. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results showed that EHL had a positive and significant effect on TSE (? = 0.747, p < 0.001) and CHLB instructional practices (? = 0.456, p < 0.001). TSE also positively influenced CHLB instructional practices (? = 0.272, p = 0.024) and partially mediated the relationship between EHL and CHLB instructional practices (? = 0.203, p = 0.031). These findings demonstrate that EHL is the primary driver of effective CHLB instructional practices, while TSE functions as a complementary psychological mechanism that translates teachers' competencies into instructional practice. The study extends the Health Literacy Framework and Social Cognitive Theory by explaining how teachers' environmental health competencies shape sustainable health-oriented teaching practices in early childhood education.